Protocol for a randomised controlled unblinded feasibility trial of HD-DRUM: a rhythmic movement training application for cognitive and motor symptoms in people with Huntington’s disease - Monica Busse; Philip Pallmann; Anne E Rosser; Robin Schubert; Derek Jones; Claudia Metzler-Baddeley; Vasileios Ioakeimidis; Cheney J G Drew; Guy B Watson; Marco Palombo (BMJ Open, 2024)
Introduction Huntington’s disease (HD) is an inherited neurodegenerative disease causing progressive cognitive and motor decline, largely due to basal ganglia (BG) atrophy. Rhythmic training offers promise as therapy to counteract BG-regulated deficits. We have developed HD-DRUM, a tablet-based app to enhance movement synchronisation skills and improve cognitive and motor abilities in people with HD. This paper outlines a randomised controlled unblinded trial protocol to determine the feasibility of a larger effectiveness trial for HD-DRUM. Additionally, the trial investigates cognitive and motor function measures, along with brain microstructure, aiming to advance our understanding of the neural mechanisms underlying training effects.Methods, design and analysis 50 individuals with HD, confirmed by genetic testing, and a Total Functional Capacity (TFC) score of 9–13, will be recruited into a two-arm randomised controlled feasibility trial. Consenting individuals with HD will be randomised to the intervention group, which entails 8 weeks of at-home usage of HD-DRUM or a usual-activity control group. All participants will undergo cognitive and motor assessments, alongside ultra-strong gradient (300 mT/m) brain microstructural MRI before and after the 8-week period. The feasibility assessment will encompass recruitment, retention, adherence and acceptability of HD-DRUM following prespecified criteria. The study will also evaluate variations in cognitive and motor performance and brain microstructure changes resulting from the intervention to determine effect size estimates for future sample size calculations.Ethics and dissemination The study has received favourable ethical opinion from the Wales Research Ethics Committee 2 (REC reference: 22/WA/0147) and is sponsored by Cardiff University (SPON1895-22) (Research Integrity, Governance and Ethics Team, Research & Innovation Services, Cardiff University, second Floor, Lakeside Building, University Hospital of Wales, Cardiff, CF14 4XW). Findings will be disseminated to researchers and clinicians in peer-reviewed publications and conference presentations, and to participants, carers and the general public via newsletters and public engagement activities. Data will be shared with the research community via the Enroll-HD platform.Trial registration number ISRCTN11906973.